Non-linear associations of 25-hydroxyvitamin D concentrations with risk of cardiovascular disease and all-cause mortality: Results from The Health Improvement Network (THIN) database. Issue 195 (December 2019) - Crowe, Francesca L; Thayakaran, Rasiah; Gittoes, Neil; Hewison, Martin; Thomas, G Neil; Scragg, Robert; Nirantharakumar, Krishnarajah
Highlights: Vitamin D status may have a non-linear association with cardiovascular disease. The shape of this association was analysed in a large cohort of 180, 263 patients. Cardiovascular disease risk increased in those with 25-hydroxyvitamin D < 35 nmol/L. Vitamin D supplements may only prevent cardiovascular disease if vitamin D is low. Abstract: Background: There is increasing evidence that vitamin D supplementation may only be beneficial in people with vitamin D deficiency, and the lack of sufficient people with very low vitamin D levels could explain the lack of protection against cardiovascular disease (CVD) reported in recent clinical trials of vitamin D supplementation. The aim of this study was to assess associations of low to moderate circulating concentrations of 25-hydroxyvitamin D (25(OH)D with risk of incident CVD and all-cause mortality, as well as the risk of ischaemic heart disease (IHD), cerebrovascular disease, and heart failure separately. Methods and Results: Longitudinal analysis of electronic health records in The Health Improvement Network (THIN), a UK primary care database. The analysis included 180, 263 patients age 18 years and older without a history of CVD and with circulating concentrations of 25(OH)D. After a mean follow-up of 2.2 (SD 1.7) years, there were 3747 patients diagnosed with CVD and 3912 patients died. Compared to patients in the highest quintile of 25(OHD) (≥ 67.5 nmol/L), those in the lowest 25(OH)D quintile (<23.1 nmol/L) had a hazard ratio (HR) of 1.24 (95% CI 1.12–1.38, P < 0.001) for CVD and 1.71 (1.55–1.88, P < 0.001) for mortality. The HR for both outcomes associated with 25(OH)D concentration was non-linear, being significantly increased in patients with 25(OH)D <35 nmol/L, and highest in those with 25(OH)D <25 nmol/L, although increased for mortality at 25(OH)D ≥100 nmol/L. The increased CVD HR in the lowest 25(OH)D quintile was more from IHD (1.35, 95% CI 1.13–1.60) and heart failure (1.38, 95% CI 1.08–1.77), than from cerebrovascular disease (1.13, 95% CI 0.97–1.31). Conclusion: Low 25(OH)D are associated with highest risk of CVD and mortality, and are consistent with accumulating evidence that increased risk of these diseases occurs primarily in people with vitamin D deficiency.